Selection of Contractor: a Flexible Performance-Based Approach - Mohamad Shukery, Nurshikin; Amirudin, Roslan; Abdul Rahiman, Nafisah; Liyana Tajul Ariffin, Hamizah; Hendra Mahmud, Syamsul (International Journal of Engineering and Technology, 2018)
Contractors are the main players in construction industry. Appropriate selection of contractor is crucial in determining the future performance of a project in any case. Sometimes this selection procedure is performed without proper consideration and deliberate methodology that it merits, thus bringing negative outcomes. This paper proposes a performance-based contractor selection approach that will empower the utilization of expertâ€™s experience and data. A flexible performance-based contractor selection system is proposed to bolster this decision-making process. To characterize and design the system, semi structured interviews and questionnaire surveys were led within public sector concentrating on the way that the selection process is carried out in practice and the evaluation connected with it. A prototype of a Flexible Performance-Based Contractor Selection System (FPCSS) was developed by using Analytical Hierarchy Process (AHP) method. The system is validated by construction industry professionals in public sector. As a conclusion, the FPCSS is a significant tool for contractor selection, by helping organizations to select a competent contractor and decrease the subjectivity of the decision-making process. The advantage as gave by the system favours a reliable indicator to predict performance of construction project by selecting a contractor based on his best performanÂ